PENGARUH PENGGUNAAN MEDIA APLIKASI WORDWALL TERHADAP MINAT BELAJAR SISWA MATA PELAJARAN MATEMATIKA - Fatah Hidayatullah; Susilahati, Susilahati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The impact of Wordwall application media on students' motivation in learning mathematics. Lack of student motivation in learning is the driving force behind this study, because instructors prefer traditional teaching techniques, such as lectures. Students complete teacher activities and questions and pay more attention to what is explained. This study aims to determine whether the use of Wordwall learning materials will increase students' enthusiasm in learning mathematics. The quantitative method is the research approach used. The findings of the study indicate that the use of Wordwall learning materials increases students' enthusiasm in learning mathematics. The results of the hypothesis test using the independent T test show that there is a difference in students' learning interest when using Wordwall application media with students' learning interest without using Wordwall application media. This can be proven by the sig. value. (2-tailed) of 0.001 <0.05, it can be concluded that the use of Wordwall application media affects students' learning interest.